2013
DOI: 10.1021/jp405041c
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Phosphate Sensing in Living Cells using Fluorescence Lifetime Imaging Microscopy (FLIM)

Abstract: Phosphate ions play important roles in signal transduction and energy storage in biological systems. However, robust chemical sensors capable of real-time quantification of phosphate anions in live cells have not been developed. The fluorescein derivative dye 9-[1-(2-methyl-4-methoxyphenyl)]-6-hydroxy-3H-xanthen-3-one (2-Me-4-OMe TG) exhibits the characteristic excited-state proton-transfer (ESPT) reaction of xanthenic derivatives at approximately physiological pH resulting in the dependence of the dye's nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 38 publications
0
42
1
Order By: Relevance
“…[5][6][7][8][9][10][11] The use of the compounds in this role emerges from their ability to occur in the electronically excited state in various structural forms (tautomeric, rotameric, protolytic) each of which have different fluorescent features (emission wavelengths, lifetimes) which depend on the properties of the medium (such as polarity, acidity/basicity, hydrogenbonding ability) or biological environment. One group of compounds that are widely used as ESPT fluorophores are hydroxyflavones (hydroxy-2-phenyl-4H-chromen-4-ones), 12 …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] The use of the compounds in this role emerges from their ability to occur in the electronically excited state in various structural forms (tautomeric, rotameric, protolytic) each of which have different fluorescent features (emission wavelengths, lifetimes) which depend on the properties of the medium (such as polarity, acidity/basicity, hydrogenbonding ability) or biological environment. One group of compounds that are widely used as ESPT fluorophores are hydroxyflavones (hydroxy-2-phenyl-4H-chromen-4-ones), 12 …”
Section: Introductionmentioning
confidence: 99%
“…8 Beyond invasive approaches employing radioactive phosphate, which are associated with a number of drawbacks, 9 there are few chemical sensors that are capable of detecting phosphate anions in an aqueous physiological system, 10 and none of them had successfully estimated the real-time concentration of phosphate inside live cells until the recently proposed xanthenic-based method. 11 Fluorescein is a complex dye that, in aqueous solution at physiological pH, can exist in mono-and dianion prototropic forms. In two pioneering papers, we showed that at nearneutral pH and in the presence of 1 M phosphate buffer, which acts as a suitable proton donor-acceptor, the excitedstate reaction that interconverts the mono-and dianion forms occurs very efficiently, and the fluorescence decays of these excited mono-and dianions become coupled, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in a recent paper, we used the ability of 2-Me-4-OMe TG to undergo phosphate-mediated ESPT to investigate the environmental phosphate concentration at physiological pH. 11 In this paper, it is shown that the dependence of the recovered long decay times from aqueous solutions of 2-Me-4-OMe TG on the phosphate concentration increases when the pH of the medium is near the pK a of the dye. Because the pK a values of 2-Me-4-OMe TG and 2-OMe-5-Me TG and related derivatives are far from the physiological pH, 21,22 it is desirable to obtain fluorescent dyes with pK a values that are higher and closer to the physiological pH than that of 2-Me-4-OMe TG.…”
Section: Introductionmentioning
confidence: 99%
“…A range of Mg 2+ lifetime probes has also been tested, but again without imaging (Szmacinski and Lakowicz, 1996). However, phosphate ions have been mapped in living cells using FLIM (Paredes et al, 2013), and nitric oxide lifetime probes have been reported, but without use in FLIM as yet (Zhegalova et al, 2013).…”
Section: Flim To Map Ion Concentrationsmentioning
confidence: 99%